2019
DOI: 10.18805/lr-4083
|View full text |Cite
|
Sign up to set email alerts
|

Divergence studies of blackgram (Vigna mungo L) for selection of drought tolerant genotypes under rainfed conditions of North Western Himalayas in J and K, India

Abstract: Present investigation was conducted in 31 groundnut accessions to assess genetic divergence, characters association involving 13 quantitative characters and path coefficients in order to identify superior accessions exhibiting higher genetic diversity. Number of pods/plant, secondary branches, kernel width, and pod yield displayed a higher level of coefficient of variation both at phenotypic and genotypic level. Genetic advance with higher heritability indicated preponderance of additive variance for pod leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…2). Similar results were reported by for plant height, seed yield/plant and 1000 seed weight in chickpea and Kumar et al (2021), Aman et al (2022) and Kumawat et al (2023) for plant height, seed yield/plant and 1000 seed weight in blackgram.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…2). Similar results were reported by for plant height, seed yield/plant and 1000 seed weight in chickpea and Kumar et al (2021), Aman et al (2022) and Kumawat et al (2023) for plant height, seed yield/plant and 1000 seed weight in blackgram.…”
supporting
confidence: 87%
“…These genotypes are desirable for rainfed conditions due to early maturity. Alike results were also showed by Kumar et al (2021) and Kumar et al (2022) for days to maturity in urdbean and mungbean under rainfed conditions, respectively.…”
mentioning
confidence: 74%
“…Plant height, 100-seed weight, days to maturity and reproductive period contributed much for diversity (Konda et al, 2007); Geetanjali et al (2015) reported that days to 50 per cent flowering, days to maturity and plant height contributed much for the diversity. While, Kumar et al (2018) reported that plant height, days to 50 per cent flowering and single plant yield contributed much for the diversity in blackgram.…”
Section: Contribution Of Different Characters Towards Divergencementioning
confidence: 99%
“…Blackgram (Mash bean) is one of the important pulse crops belongs to the Papilionaceae family (Mohanlal et al 2021). The crop has genetic diversity for its growth and yield (Kumar et al 2021;Priya et al 2021). Legume plants are efficient in biological nitrogen fixation (BNF).…”
Section: Introductionmentioning
confidence: 99%